Safety and utilisation of AZD1222 (ChAdOx1 nCoV-19) COVID-19 vaccine: a UK post-authorisation active surveillance study - Evans, Alison; Roy, Debabrata; Davies, Miranda; Dhanda, Sandeep; Morris, Denise; Aurelius, Taylor; Lane, Samantha; Fry, Catherine; Shakir, Saad (BMJ open, 2025)
ObjectivesTo monitor the safety and utilisation of AZD1222 under real-world use in the UK.DesignA non-interventional post-authorisation active surveillance study.SettingVaccination sites in the UK.ParticipantsA total of 17 945 participants were eligible and provided consent to participate in the study between 1 March 2021 and 6 April 2023. Participants were followed up at weeks 1, 4 and 14 and at months 6, 9, 12 and 18 after the first dose of AZD1222 vaccination and prompted to complete electronic data capture forms. A total of 11 219 participants submitted a Follow-Up 1 form and 5189 participants submitted a Follow-Up 7 form (at 18 months).Primary and secondary outcome measuresThe safety of AZD1222, including the identification, assessment and quantification of serious adverse events (SAEs) and adverse events of special interest (AESI), was examined. The utilisation of AZD1222 was described and characterised, including populations with missing information.ResultsThe majority of participants were women (n=10 845; 60.4%) and the median age (IQR) was 50 (43, 62) years. Most participants were from white ethnic groups (n=13 112; 73.1%). Headache and fatigue had the highest reported incidence rate (421.28 cases per 1000 person years and 386.00 cases per 1000 person years, respectively). The most frequently reported AESI was anosmia (6.25 cases per 1000 person years). An increased Observed versus Expected (O:E) ratio was seen for anaphylaxis (O:E 7.38 (95% CI 2.80 to 11.95); based on 10 observed cases (expected cases: 1.36)) and anosmia and/or ageusia (O:E 39.23 (95% CI 29.13 to 49.32), based on 58 observed cases (expected cases: 1.48)).ConclusionsThe most frequent vaccinee-reported adverse events (AEs) were headache and fatigue. An increased O:E ratio was seen for the AEs of anaphylaxis and anosmia and/or ageusia. No safety signals were identified throughout the course of this study.Trial registration numberThis study is registered with the HMA-EMA Catalogue of RWD studies (EUPAS44035).